Perspectives on the evolving state of the art management of gastrointestinal stromal tumours - Szucs, Zoltan; Jones, Robin L. (Translational Gastroenterology and Hepatology; Vol 3 (April 2018): Translational Gastroenterology and Hepatology, 2018)
Gastrointestinal stromal tumours (GISTs) represent a very exciting tumour entity for the medical oncologist. There has been extensive clinical and preclinical research dissecting the natural behaviour, molecular landscape and therapeutic responsiveness of this rare mesenchymal tumour. Various molecular subtypes of GIST have a differing prognostic and predictive relevance in the state of the art management of the disease. Emerging mature clinical trial data gathered over the last one and half decade provided substantial molecular profiling information in understanding the success and eventual failure of treatment. In our review of the most relevant literature we aim to guide the clinician in tailoring neoadjuvant, adjuvant and palliative treatment of GIST alongside the different, now well established molecular subgroups of GISTs.